Pengaruh Perilaku Beragama Terhadap Prestasi Belajar Siswa di MTs. Salafiyah Mojogeneng Mojokerto - Umi Chorida; Muchammad Lubbil Khobir (Educational Research Indonesia, 2025)
The purpose of this study is to evaluate how religious behavior affects student learning achievement at MTs Salafiyah Mojogeneng Mojokerto. This study used a quantitative approach, and data were collected through questionnaires and documentation of report cards (variable X: religious behavior). The research sample consisted of 64 students out of 427 students. To determine the relationship between the two variables, the data were analyzed using Pearson's Product Moment correlation. The results showed that students' religious behavior was good (score 79.56) and learning achievement was good (score 76.66). The correlation analysis found a coefficient of r = 0.8002, which indicates a strong positive relationship between the two. This result shows that students' learning achievement increases along with their religious behavior. The theory reinforced by this study is that the internalization of religious values can have an impact on spiritual (SQ), emotional (EQ), and intellectual (IQ) intelligence, all of which impact academic success. Thus, faith-based educational institutions such as pesantren have the ability to maximize religious character development to support students' academic progress.